Social Based Layouts for the Increase of Locality in Graph Operations - Prat-Pérez, Arnau; Dominguez-Sal, David; Larriba-Pey, Josep L. (Database Systems for Advanced Applications, 2011)
Graphs provide a natural data representation for analyzing the relationships among entities in many application areas. Since the analysis algorithms perform memory intensive operations, it is important that the graph layout is adapted to take advantage of the memory hierarchy. Here, we propose layout strategies based on community detection to improve the in-memory data locality of generic graph algorithms. We conclude that the detection of communities in a graph provides a layout strategy that improves the performance of graph algorithms consistently over other state of the art strategies.